Public Cemetery Land Management Policy in Sidoarjo Regency - Cynthia Nanda Sari; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2022)
This research aims to analyze and describe the implementation of public burial land management policies for villagers in Ban Village as well as factors that affect the implementation of public burial land management policies for villagers in Ban Village. This study is a qualitative descriptive study using purposive sampling techniques in determining informants. Data collection techniques with observations, interviews, and documentation. Data analysis techniques use an interactive approach from Miles and Hubeman consisting of four components of analysis namely; data collection, data reduction, data presentation, and conclusion withdrawal. The dimension of the organization's activities has not been maximized even though the coordination of each implemtator exists but there are still people who are not aware of this policy. The behavioral dimensions of policy implementing agents are in accordance with the concept of Van Meter and Van Horn which has procedural performance for the successful implementation of this public burial land management policy. Economic, social, cultural dimensions see the need for a review of the policy of managing public burial land this looks at the condition of rural communities that have changed in terms of economy, habits, lifestyle. Factors that influence the implementation of this policy are encountered by researchers on the age and type of education, gender, and knowledge and understanding that points to each individual in determining the preferences taken as a basis for determining attitudes on existing policies.